Evaluation of BSI Stock Investment Strategy Based on a Fundamental Approach - Muliyani (Al-Mashrof: Islamic Banking and Finance, 2025)
This study aims to analyze the financial performance of Bank Syariah Indonesia (BSI) using a fundamental analysis approach during the 2020–2025 period. The main focus lies in evaluating financial indicators such as Earnings per Share (EPS), Return on Equity (ROE), Price to Earnings Ratio (PER), and dividend policy, and their relevance to investment decisions. The analysis reveals that BSI recorded significant growth in EPS and ROE, reflecting improved managerial efficiency and profitability following post-merger consolidation. The decline in PER up to 2022, followed by stabilization in subsequent years, indicates that the stock valuation began to reflect its actual fundamentals. On the other hand, the fluctuating dividend policy with a low Dividend Payout Ratio (DPR) suggests a corporate strategy more oriented toward long-term growth rather than immediate profit distribution. These findings support signaling theory, where financial performance and corporate policies serve as signals to investors in assessing a stock’s prospects and risks. Therefore, fundamental analysis proves to be an essential tool for investors in evaluating the viability of BSI’s stock as a prospective long-term investment instrument. Keywords: Bank Syariah Indonesia, fundamental analysis, stock valuation, signaling theory, investment decision